Rapid fabrication of TiO2@carboxymethyl cellulose coatings capable of shielding UV, antifog and delaying support aging. (1st August 2017) - Li, Xiaozhou; Lv, Junping; Li, Dehuai; Wang, Lin
Highlights: Stable and small TiO2 @CMC NPs were handily obtained by a one-pot microwave synthesis. CMC can effectively shield the photocatalytic active sites of TiO2 . (PEI/TiO2 @CMC)*15 coating can shield UV and delay the aging of their supports. (PEI/TiO2 @CMC)*15 coating shows antifogging and visible light-filtering abilities. Highly effective and safe UV-screening TiO2 coating is used for agricultural films. Abstract: Agricultural plastic films capable of shielding UV, filtering visible light and antifog are important to prolong their life and protect safeties of agriculturists and crops. In this work, high stable and small size TiO2 @polymer nanoparticles (NPs) were prepared by an efficient one-pot microwave synthesis using titanic sulfate as Ti resource, carboxymethyl cellulose sodium (CMC) as complexing agent and stabilizer. The TiO2 @CMC NPs obtained were then utilized to fabricate poly(ethylene imine) (PEI)/TiO2 @CMC coatings on the surface of polypropylene films by a layer-by-layer assembly technique. The TiO2 @CMC NPs show rapid deposition rate because small, spherical and anion-rich TiO2 @CMC NPs possess large specific surface area and fast diffusion rate. More importantly, property experiments confirm that (PEI/TiO2 @CMC)*15 coatings can not only effectively shield UV rays, filter visible light and prevent fogging but also delay the aging of their supports.